2004
DOI: 10.1108/03068290410550638
|View full text |Cite
|
Sign up to set email alerts
|

The role of institutions in the development process of African countries

Abstract: This paper examines the role of institutions in the development process of African countries. It has been show that, whereas institutions have played a greater role in the economic development of several East Asian countries, in Africa they are weaker and ineffective because of poor enforcement of the rule of law, corruption, mismanagement, absence of strong civil society and political interference. It is argued that well-functioning institutions can promote growth and reduce poverty in Africa by providing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Research focused on the relationship between rule of law and economic development performed by the World Bank and the US's CIA found that there is a proportional increase in rule of law and social wealth. found that the likelihood of a high rule of law country enjoying higher income is 29/34 (85.29%), a finding that coincides with other scholarly views (Bashir, 2002;Kumssa & Mbeche, 2004;Krever, 2011;Osman, Alexiou, & Tsaliki, 2011) (one exceptional case was (Osman et al, 2011)). As concluded by The Economist (2008), the general view of scholarship is that "rule of law has become the motherhood and apple pie of development economics."…”
Section: A Scholar's View Of the Relationship Between Rule Of Law Andsupporting
confidence: 66%
“…Research focused on the relationship between rule of law and economic development performed by the World Bank and the US's CIA found that there is a proportional increase in rule of law and social wealth. found that the likelihood of a high rule of law country enjoying higher income is 29/34 (85.29%), a finding that coincides with other scholarly views (Bashir, 2002;Kumssa & Mbeche, 2004;Krever, 2011;Osman, Alexiou, & Tsaliki, 2011) (one exceptional case was (Osman et al, 2011)). As concluded by The Economist (2008), the general view of scholarship is that "rule of law has become the motherhood and apple pie of development economics."…”
Section: A Scholar's View Of the Relationship Between Rule Of Law Andsupporting
confidence: 66%
“…It has been found that communities with high levels and diverse supply of social Maina et al 155 capital are better able to deal with poverty, vulnerability, disputes and also to take advantage of new opportunities (Woolcock and Narayan, 2000). Social cohesion ensures that the community will pull together to initiate mechanisms for self support and in provision of necessary resources and services (Kummssa and Mbeche, 2004;Amudavi, 2005). Such cohesion is favourable to peaceful co-existence.…”
Section: Resultsmentioning
confidence: 99%
“…They have become structurally weak; they are left with authoritarian development regimes with only partially modernized economic structures and dysfunctional political regulation leading to conflicts (Köhler 2018). According to Kumssa and Mbeche (2004), institutions in Africa have played a weaker role "because of poor enforcement of the rule of law, corruption, mismanagement, the absence of strong civil society and political interference" (Mbeche 2004, 840).…”
Section: Weak Institutions and Weak Paradigmsmentioning
confidence: 99%